Two-parameter characterization of chromosome-scale recombination rate - Li, Wentian; Freudenberg, Jan (Genome Research, 2009)
The genome-wide recombination rate (RR) of a species is often described by one parameter, the ratio between total genetic map length (G) and physical map length (P), measured in centimorgans per megabase (cM/Mb). The value of this parameter varies greatly between species, but the cause for these differences is not entirely clear. A constraining factor of overall RR in a species, which may cause increased RR for smaller chromosomes, is the requirement of at least one chiasma per chromosome (or chromosome arm) per meiosis. In the present study, we quantify the relative excess of recombination events on smaller chromosomes by a linear regression model, which relates the genetic length of chromosomes to their physical length. We find for several species that the two-parameter regression, G = G0 + k · P , provides a better characterization of the relationship between genetic and physical map length than the one-parameter regression that runs through the origin. A nonzero intercept (G0) indicates a relative excess of recombination on smaller chromosomes in a genome. Given G0, the parameter k predicts the increase of genetic map length over the increase of physical map length. The observed values of G0 have a similar magnitude for diverse species, whereas k varies by two orders of magnitude. The implications of this strategy for the genetic maps of human, mouse, rat, chicken, honeybee, worm, and yeast are discussed.